STRATEGIC DIRECTIONS FOR THE MATURATION AND IMPLEMENTATION OF ISLAMIC FINANCIAL SERVICES IN COMMERCIAL BANKS OF UZBEKISTAN (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article discusses the features of the development of the Islamic banking sector, the principles of the Islamic financial institutions, as well as financial instruments that are used within the Islamic financial system. The distinctive features of Islamic and traditional banks are analyzed and the current state of development of Islamic finance in the global economy was studied. In addition, the main directions of the development of Islamic finance in the Republic of Uzbekistan are presented.